Faces of Muhammad: western perceptions of the prophet of Islam from the middle ages to today by John V. Tolan.Princeton, USA: Princeton University Press, 2019. Pp. 311. ISBN: 9780691167060 - Akhmetova, Elmira (The Islamic Foundation, 2020)
This is a review of the book entitled FACES OF MUHAMMAD: WESTERN PERCEPTIONS OF THE PROPHET OF ISLAM FROM THE MIDDLE AGES TO TODAY written by John V. Tolan.